2024
DOI: 10.1039/d3fo04240e
|View full text |Cite
|
Sign up to set email alerts
|

Dietary oleacein, a secoiridoid from extra virgin olive oil, prevents collagen-induced arthritis in mice

María Ángeles Rosillo,
Isabel Villegas,
Victoria Vázquez-Román
et al.

Abstract: Olacein (OLA), one of the main secoiridoids derived from extra virgin olive oil (EVOO), has been shown to modulate oxidative and inflammatory responses in various pathological conditions; however, its potential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Several studies have focused on EVOO and its compounds, showing beneficial effects on body weight (quantitative reduction) [ 112 ], adipose tissue (quantitative reduction and positive metabolic modulation) [ 113 , 114 ], lipidic ratio (reduction of total cholesterol (TC), TC/high-density lipoproteins (HDL), and low-density lipoprotein (LDL) oxidation; increase of HDL concentrations) [ 115 , 116 ], glycemic metabolism (reduction of T2DM incidence, fasting glucose, and advanced glycosylated end-products, including glycated hemoglobin; activation of the glucagon-like peptide-1 (GLP-1) incretin-pattern) [ 117 , 118 , 119 , 120 ], and cardiovascular risk (reduction of LDL oxidation, systolic blood pressure, and cardiovascular events, improvement of nitric oxide (NO)-mediated endothelial function) [ 121 , 122 , 123 , 124 ]. To a further extent, but with a lesser degree of evidence (mostly preclinical studies), EVOO intake showed effectiveness in the reduction/modulation of autoimmune [ 125 , 126 , 127 , 128 , 129 ], inflammatory bowel [ 130 , 131 , 132 , 133 ], neurodegenerative [ 134 , 135 , 136 , 137 , 138 ], and neoplastic diseases [ 137 , 139 , 140 ], as well as gut microbiota alterations [ 141 , 142 , 143 , 144 ].…”
Section: The Role Of Lifestyle Modificationsmentioning
confidence: 99%
“…Several studies have focused on EVOO and its compounds, showing beneficial effects on body weight (quantitative reduction) [ 112 ], adipose tissue (quantitative reduction and positive metabolic modulation) [ 113 , 114 ], lipidic ratio (reduction of total cholesterol (TC), TC/high-density lipoproteins (HDL), and low-density lipoprotein (LDL) oxidation; increase of HDL concentrations) [ 115 , 116 ], glycemic metabolism (reduction of T2DM incidence, fasting glucose, and advanced glycosylated end-products, including glycated hemoglobin; activation of the glucagon-like peptide-1 (GLP-1) incretin-pattern) [ 117 , 118 , 119 , 120 ], and cardiovascular risk (reduction of LDL oxidation, systolic blood pressure, and cardiovascular events, improvement of nitric oxide (NO)-mediated endothelial function) [ 121 , 122 , 123 , 124 ]. To a further extent, but with a lesser degree of evidence (mostly preclinical studies), EVOO intake showed effectiveness in the reduction/modulation of autoimmune [ 125 , 126 , 127 , 128 , 129 ], inflammatory bowel [ 130 , 131 , 132 , 133 ], neurodegenerative [ 134 , 135 , 136 , 137 , 138 ], and neoplastic diseases [ 137 , 139 , 140 ], as well as gut microbiota alterations [ 141 , 142 , 143 , 144 ].…”
Section: The Role Of Lifestyle Modificationsmentioning
confidence: 99%